2015
DOI: 10.1371/journal.pone.0117016
|View full text |Cite
|
Sign up to set email alerts
|

Increased Classical Endoplasmic Reticulum Stress Is Sufficient to Reduce Chondrocyte Proliferation Rate in the Growth Plate and Decrease Bone Growth

Abstract: Mutations in genes encoding cartilage oligomeric matrix protein and matrilin-3 cause a spectrum of chondrodysplasias called multiple epiphyseal dysplasia (MED) and pseudoachondroplasia (PSACH). The majority of these diseases feature classical endoplasmic reticulum (ER) stress and activation of the unfolded protein response (UPR) as a result of misfolding of the mutant protein. However, the importance and the pathological contribution of ER stress in the disease pathogenesis are unknown. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…The ER stress system is typically activated in response to stressors, including excessive amounts of unfolded proteins in the ER. ER stress response in PD was recently reported (Domon et al, 2009;Kung et al, 2015;Yamada et al, 2015). These authors suggested that modulation of the ER stress system could have therapeutic effects.…”
Section: Discussionmentioning
confidence: 95%
“…The ER stress system is typically activated in response to stressors, including excessive amounts of unfolded proteins in the ER. ER stress response in PD was recently reported (Domon et al, 2009;Kung et al, 2015;Yamada et al, 2015). These authors suggested that modulation of the ER stress system could have therapeutic effects.…”
Section: Discussionmentioning
confidence: 95%
“…During development, however, it also negatively impacts chondrocyte proliferation and the longitudinal growth of long bones, independently of ECM abnormalities [38]. The Dmm/+ mouse displays UPR activation in articular chondrocytes prior to the onset of OA [28].…”
Section: A Role For the Unfolded Protein Response In Chondrodystromentioning
confidence: 99%
“…Interestingly, BiP expression was markedly increased after DMM surgery in wild-type mice, clearly demonstrating an involvement of ER stress and the UPR in the pathogenesis of OA. However, whilst BiP levels were also increased upon DMM surgery in the transgenic mice overexpressing a misfolding variant of thyroglobulin (Tg cog ) under the Col2a1 promoter (ColIITg cog , a model of cartilage-specific ER stress 51 ), the onset of OA was delayed, and a delay in cartilage apoptosis and damage was seen two weeks after surgery compared with wild-type controls. Interestingly, ColIITg cog mice had elevated BiP protein levels prior to DMM surgery, and the prosurvival Xbp1-associated UPR signalling network was activated in ColIITg cog mice after DMM, suggesting that pre-exposure to ER stress or activation of the specific pro-survival UPR responses such as the Xbp1s signalling could be chondroprotective.…”
Section: Chondrocyte Endoplasmic Reticulum Stress In Osteoarthritismentioning
confidence: 99%